Analisa Loss Time untuk Meningkatkan Produktivitas pada PT. PMI - Kevin Leonardo Takaria; Prayonne Adi (Jurnal Titra, 2019)
PT Panasonic Manufacturing Indonesia (PMI) is one of the pioneers of the most successful electronics industry at local and abroad. One of the existing Business Unit (BU), Audio BU, is always doing improvements, especially in the PQA section where productivity improvements always done. This research by analyzing invisible loss time or not realized by the company at Final Assembly 5 with PDCA approach. The total detected were 22 items loss with the estimated total loss time in July as many as  2,680 minutes with estimated P/H/H 6.64. Improvements succeeded in reducing loss time by 1,574.99 minutes with P/H/H increasing to 6.72. These improvements have also been successful saving cost of Rp 2,910,859.26.